Sleep characteristics and progression of coronary artery calcification: Results from the Heinz Nixdorf Recall cohort study. (April 2018) - Kowall, Bernd; Lehmann, Nils; Mahabadi, Amir-Abbas; Lehnich, Anna-Therese; Moebus, Susanne; Budde, Thomas; Seibel, Rainer; Grönemeyer, Dietrich; Erbel, Raimund; Jöckel, Karl-Heinz; Stang, Andreas
Abstract: Background and aims: Sleep characteristics are associated with incident cardiovascular diseases (CVD), but there is a lack of studies on the association between sleep characteristics and incidence/progression of coronary artery calcification (CAC). Methods: In the Heinz Nixdorf Recall Study, a population-based cohort study in Germany, CAC was assessed by electron-beam tomography at baseline and at 5-year follow-up. In an analysis set of 3043 subjects (age at baseline 45–74 years; 47% men), we fitted logistic and linear regression models to assess associations between self-rated sleep characteristics (nocturnal and total sleep duration; napping; various sleep disorders) and CAC incidence/CAC progression. Progression was measured as 5-year progression factor, as categories of absolute CAC change, and additionally characterized as rapid or slow compared to an extrapolation of baseline CAC values. Results: We observed barely any association between sleep characteristics and CAC progression regardless of the chosen statistical approach; associations between sleep and CAC incidence were slightly larger, e.g., the geometric mean of the 5-year CAC progression factor was 6.8% (95% confidence interval: −9.5; 25.9) larger for ≤5 h, 2.9% (−7.3; 14.3) larger for 5.1–6.9 h and 7.1% (−2.4; 15.7) smaller for ≥7.5 h total sleep compared to 7- <7.5 h total sleep. For subjects with any regular sleep disorder, the geometric mean of the 5-year CAC progression was 3.5% (−4.7; 11.2) smaller compared to subjects without any regular sleep disorder. Conclusions: In this German cohort study, sleep characteristics were barely associated with CAC progression. Highlights: About two thirds of the participants of our older study group had coronary artery calcification at baseline. Among persons free of CAC at baseline, sleep characteristics were slightly associated with onset of CAC. Sleep characteristics were barely associated with CAC progression.